Coexistence of breast hemangioma with fibroadenoma: a rare case report - Rajdeo, Roma Nirmalkumar; Umap, Pradeep S.; Bajaj, Jitin; Shrikhande, Anuradha V. (International Journal of Research in Medical Sciences, 2017)
Vascular tumors of the breast are uncommon and include angiosarcomas and hemangiomas. Angiosarcomas are more common and benign hemangiomas are rare. We report a case of 16 years old female patient with hemangioma of breast coexisting with very commonly occurring breast fibroadenoma. The rarity of literature on breast hemangioma especially coexistent with fibroadenoma, and its importance in differentiation from the more common malignant counterpart, the angiosarcomas deserves mention.